The filarial and the antibiotics: Single or combination therapy using antibiotics for filariasis - Fordjour, Fatima Amponsah; Kwarteng, Alexander (Frontiers in Cellular and Infection Microbiology, 2022)
Filarial infections caused by nematodes are one of the major neglected tropical diseases with public health concern. Although there is significant decrease in microfilariae (mf) prevalence following mass drug administration (IVM/DEC/ALB administration), this is transient, in that there is reported microfilaria repopulation 6-12 months after treatment. Wolbachia bacteria have been recommended as a novel target presenting antibiotic-based treatment for filarial disease. Potency of antibiotics against filarial diseases is undoubtful, however, the duration for treatment remains a hurdle yet to be overcome in filarial disease treatment.